Viscosity Measurements of Binary and Multicomponent Refrigerant Mixtures Containing HFC-32, HFC-125, HFC-134a, HFO-1234yf, and CO2 - Yang, Xiaoxian; Arami-Niya, Arash; Xiao, Xiong; Kim, Dongchan; Al Ghafri, Saif ZS; Tsuji, Tomoya; Tanaka, Yukio; Seiki, Yoshio; May, Eric F (American Chemical Society, 2020)
Viscosity measurements of ten refrigerant mixtures were conducted in the homogeneous liquid and gas phases with a vibrating-wire viscometer in the temperature range from (233 to 373) K at pressures up to 10.0 MPa. The investigated mixtures include eight equimolar binaries (R32 + R125, R32 + R134a, R32 + CO2, R125 + R134a, R125 + CO2, R134a + R1234yf, R134a + CO2, and R1234yf + CO2) and two multicomponent mixtures (R32 + R1234yf + CO2 and R32 + R125 + R134a + R1234yf + CO2). The viscometer was calibrated with the measurements of pure carbon dioxide in both liquid and gas phases and verified with pure R32 and R125 measurements. The relative combined expanded uncertainties (k = 2) in the experimental viscosity are from (3.3 to 5.2) %. The relative deviations of the measured viscosities from values calculated with the extended corresponding states (ECS) model implemented in the REFPROP 10.0 software package were generally within 10%. The measured viscosities of binaries were used to tune the binary interaction parameters in the ECS model, and the model with the optimized parameters agreed with the experimental data of all investigated mixtures within 6% with significant improvements observed in the liquid phase.